Science on tap: pouring knowledge into the local community - Barrett, Margaux; Santoro, Jennifer; Jeffords, Chris (Frontiers in Communication, 2024)
Recently, science communication efforts have focused increasingly on sharing research findings with a broader audience. Since its creation in 2010, Science on Tap (SoT) has realized this goal by recruiting scientific professionals from diverse disciplines to share their latest research findings with the general public in a laid-back pub or brewery setting to bridge the gap between perceived “ivory tower” knowledge and public perception. In the past decade, local SoT chapters have been created across the world, including our own program started in 2022 in Phoenixville, Pennsylvania, to act as these science boundary spanners. To gauge interest and increase the relevancy of our program, we conducted a descriptive survey of our SoT attendees and received 50 responses. Results indicate that attendees have learned a fair amount of new knowledge from these talks and are primarily drawn in by the topic and speaker. Participants are especially engaged in locally relevant topics such as environmental issues and report the highest enjoyment from learning new information in a relaxed brewery atmosphere. In sum, topics and location have helped our program to be an effective science communication boundary spanner in this community.